An Investigation of Islamic Students' Learning Habits - Akrim Akrim (AL-ISHLAH: Jurnal Pendidikan, 2021)
Students at a High School in Medan, North Sumatra, who are taking part in an Islamic Education program, are being studied to determine which factors influence their learning habits. Descriptive research is used in this study. During January and February 2020, this study was carried out. This study included 212 students from XI and XII levels. In this study, questionnaires were used to collect data on students' following Islamic Education classes. Islamic education subjects in grades XI and XII were the most popular subjects for students to join a working group on. At the same time, independent study at home was the least popular learning method.